Biomodulation of inflammatory cytokines related to oral mucositis by low-level laser therapy - Basso, Fernanda G. [UNESP]; Pansani, Taisa N. [UNESP]; Soares, Diana G. [UNESP]; Scheffel, Débora L. [UNESP]; Bagnato, Vanderlei S.; Costa, Carlos Alberto de Souza [UNESP]; Hebling, Josimeri [UNESP] (Wiley, 2015)
This study evaluated the effects of LLLT on the expressionof inﬂammatory cytokines related to the development of oralmucositis by gingival ﬁbroblasts. Primary gingival ﬁbroblastswere seeded on 24-well plates (105cells/well) for 24 h. Freshserum-free culture medium (DMEM) was then added, andcells were placed in contact with LPS (Escherichia coli,1 lgmL1), followed by LLLT irradiation (LaserTABLE—InGaAsP diode prototype—780 nm, 25 mW) delivering 0,0.5, 1.5 or 3 J cm². Cells without contact with LPS werealso irradiated with the same energy densities. Gene expres-sion of TNF- a, IL-1b, IL-6 and IL-8 was evaluated by Real-Time PCR, and protein synthesis of these cytokines wasdetermined by enzyme-linked immunosorbent (ELISA) assay.Data were statistically analyzed by the Kruskal– Wallis test,complemented by the Mann–Whitney test (P < 0.05). LPStreatment increased the gene expression and protein synthesisof TNF-a, IL-6 and IL-8, while the expression of IL-1b wasnot affected. For LPS-treated groups, LLLT promoted signif-icant decreases in the expression of TNF-a, IL-6, and IL-8 at1.5 J cm2and 3 J cm2. These results demonstrate thatLLLT promoted a beneﬁcial biomodulatory effect on theexpression of inﬂammatory cytokines related to oral mucosi-tis by human gingival ﬁbroblasts.